2018
DOI: 10.1002/ejsp.2512
|View full text |Cite
|
Sign up to set email alerts
|

Need for closure and compensatory rule‐based perception: The role of information consistency

Abstract: When making comparisons, people tend to use routinized standards, rules, and knowledge structures. Compensatory rules (e.g., “if competent, then cold”, “if incompetent, then warm”) allow for the quick and easy evaluation of groups when they are compared. We claim that the application of these rules is especially attractive for people who are motivated to seek quick and firm answers (people high in the need for closure—NFC). However, we assume that when people are confronted with expectancy‐inconsistent informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In this study, the researchers demonstrated that low trust in one's own capacity to achieve certainty may lead to cognition that is typically associated with openness, such as reduced bias in the formulation of impressions of others, the taking of complex decisions rather than simple ones, and reduced stereotyping. In addition, studies in which one's confidence in the previously obtained knowledge was experimentally undermined, these open-minded effects were also found (Dragon & Kossowska, 2019). In these situations, individuals lost faith in themselves and their knowledge, which, in turn, resulted in this knowledge (i.e.…”
Section: A Goal (Versus Means) Perspective On the Quest For Certaintymentioning
confidence: 98%
“…In this study, the researchers demonstrated that low trust in one's own capacity to achieve certainty may lead to cognition that is typically associated with openness, such as reduced bias in the formulation of impressions of others, the taking of complex decisions rather than simple ones, and reduced stereotyping. In addition, studies in which one's confidence in the previously obtained knowledge was experimentally undermined, these open-minded effects were also found (Dragon & Kossowska, 2019). In these situations, individuals lost faith in themselves and their knowledge, which, in turn, resulted in this knowledge (i.e.…”
Section: A Goal (Versus Means) Perspective On the Quest For Certaintymentioning
confidence: 98%